The Use of Flip Chart as a Tool to Strengthen Scientific Literacy at Junior High School Student - Yen Sastri; Evi Suryawati; Mariani Natalina L; Muhammad Hatta (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
This research aims to determine the effect of using a flip chart on students' scientific literacy on environmental pollution material. This development research used the ADDIE model. This research was carried out until the development phase. The flip chart that has been produced was validated by using validation sheets by 4 validators who experts on media and material, then tested on 20 grade VIII junior high school students. The data of Students' responses about flip chart were collected by using a questionnaire and students' science literacy were collected by using the multiple-choice test. The results of the research indicated that there was an increase in the mean score of pre-test and post-test from 62 (low) to 81 (high). It illustrated that there was a strengthening of science literacy on the competence to explain phenomena scientifically from 61.25% (low) to 87.5% (very good), the competence to design and evaluate scientific inquiry from 53.75% (low) to 71.25% (enough), and the competence to interpret data and evidence scientifically from 80% (good) to 87.5% (very good). This result was supported by student questionnaires when using a flip chart, which is 88.1, it shows that flip charts can be used as a means of strengthening student scientific literacy